Slowdown means the end of pervasive capitalism - Dorling, D (Dünya, 2023)
Danny Dorling discusses the end of the age of speed in his book Slowdown. While examining the phenomenon of “slower progress” in the face of the ever-increasing population, workforce and capital in the world under the spell of progress, it draws attention to sustainable solution steps that can be taken in line with future expectations.